Penghubung Komisi Yudisial Jateng dan Partisipasi Publik: Studi Keberadaan Sahabat Komisi Yudisial di Jawa Tengah - Dardiri, Ahmadi H; Fahrurrosin, Fahrurrosin (JURNAL HUKUM PELITA, 2025)
This study aims to determine the existence of Sahabat Komisi Yudisial (SKY) in Central Java which is in the working area of the Central Java Penghubung Komisi Yudisial (PKY). The existence of SKY is not found juridically in the regulations on the Judicial Commission, but its existence in several regions, namely the city of Semarang, Salatiga and Pekalongan, is very significant for PKY Central Java in helping networks in the regions, so the author wants to research the existence of SKY using the theory of public participation. This research is a qualitative research with a descriptive-analytic approach. The data obtained in the field about SKY in Central Java is analyzed using the theory of public participation. The results of this study state that public participation in the existence of SKY in Central Java is at the level of public collaboration. This level is the fourth level after the level of public demands (insisted publics), networked publics, invited publics. while at the level of public action (doing public) in supervising judges has not been able to run well due to the immaturity of knowledge and courage of SKY personnel in supervising judges independently